Clinical Symptoms, Hemoglobin Levels, and Chest Radiography in Pulmonary Tuberculosis Patients - Nur Alam Syafar; Rasfayanah Rasfayanah; Rahmawati Rahmawati; Shofiyah Latief; Indah Lestari Daeng Kanang (Muhammadiyah Medical Journal, 2026)
Background: Pulmonary tuberculosis remains a major global health problem with high morbidity and mortality. Clinical symptoms, haemoglobin levels, and chest radiograph findings are important indicators of disease severity and physiological impact, making their relationship relevant for early assessment and clinical management. Purpose: This study aimed to analyse the relationship between clinical symptoms, haemoglobin levels, and chest radiograph findings among patients with pulmonary tuberculosis at Ibnu Sina YW-UMI Hospital Makassar in 2023–2024. Methods: This cross-sectional analytic observational study used total sampling and included 100 pulmonary tuberculosis patients who met the inclusion criteria. Clinical symptoms, haemoglobin levels, and chest radiographs were collected from medical records. Univariate and Chi-square bivariate analyses were performed, with p < 0.05 considered significant. Results: Most patients had decreased haemoglobin levels (81%) and far advanced radiographic lesions (81%). Common clinical symptoms were productive cough (86%), shortness of breath (75%), fever (77%), decreased appetite (59%), and weight loss (69%). Only shortness of breath (p = 0.000) and decreased appetite (p = 0.029) were significantly associated with haemoglobin levels. In contrast, all clinical symptoms showed significant associations with chest radiographic severity. Conclusion: Shortness of breath and decreased appetite were significantly associated with decreased haemoglobin levels in pulmonary tuberculosis patients, while other symptoms showed no significant association. All clinical symptoms were significantly associated with chest radiographic severity. Most patients also had anemia and far advanced radiographic lesions, indicating advanced disease.